Structural change and industrial upgrading in the Philippines: Stylized facts and routes towards sophisticated economic diversification - Edylinda Annette Oreta Pelkmans-Balaoing; Adrian Mendoza (University of the Philippines, School of Economics (UPSE), 2024)
Using time series data from 1945 to 2023, this paper develops stylized facts to trace the historical origins of the Philippines' narrow economic base. Econometric models are then estimated to analyze the drivers and benefits of economic diversification in the Philippines. The empirical results suggest that reindustrializing the domestic production base can significantly enhance economic diversification. Strategies that accelerate the growth of local industries, especially to catch up with the dominant services sector, are vital. Effective policies should focus on developing physical and human capital, improving connectivity, and fostering domestic innovation. This push for greater diversification is justified by its potential benefits on output and growth stability, and diversification and growth of exports. The paper also explores various routes towards economic diversification and industrial upgrading in the Philippines using the product space approach. The first route is directed towards leapfrogging to a more sophisticated economic structure in the product space. The second route points at climbing the value ladder within global value chains. The third route leads to the strengthening of the local industrial base that is heavily populated by small and mediumsized establishments.
Keywords: L16; O14; O25; O33; 330; economic diversification; industrial upgrading; structural transformation; manufacturing; exports; product space; global value chains; SMEs; Philippines